DOP12 Mutations in the X-linked inhibitor of apoptosis protein promote susceptibility to microbiota-induced intestinal inflammation. (25th January 2019) - Gopalakrishnan, S; Zeissig, Y; Strigli, A; Basic, M; Hartwig, J; Wang, J; Muders, M; Barreton, G; Baines, J F; Bleich, A; Hampe, J; Zeissig, S
Abstract: Background: Mendelian forms of IBD have provided novel insight into the mechanisms underlying intestinal inflammation in IBD. We and others have recently described mutations in the gene encoding X-linked inhibitor of apoptosis protein (XIAP) as the basis for a novel Mendelian form of Crohn's disease (CD). However, the mechanisms through which XIAP deficiency promotes intestinal inflammation are unknown. Here, we investigated the pathways that link XIAP defects and intestinal inflammation using mice deficient in XIAP. Methods: Xiap −/− mice and wild-type (WT) littermates were analysed under constitutive conditions as well as upon exposure to the pathobiont Helicobacter hepaticus . Results: Xiap −/− mice showed a reduced number of Paneth cells (PCs) in the ileum as a consequence of increased PC death, in line with the role of XIAP as an inhibitor of effector caspases. Increased cell death was specific to PCs and not observed for other secretory or absorptive intestinal epithelial cells. The loss of PCs was associated with reduced abundance of antimicrobial peptides in the ileum and colon, impaired bacterial control, and dense colonisation of intestinal crypts by commensal bacteria as well as an increased number of mucosa-adherent bacteria. In addition, we observed alterations in the composition of the microbiota in Xiap −/− mice with an increased relative abundance of Deltaproteobacteria including increased abundance of the pathobiont Bilophila wadsworthia . While these alterations in PCs and bacterial control were insufficient to elicit spontaneous intestinal inflammation under specific pathogen-free (SPF) conditions, exposure to the pathobiont Helicobacter hepaticus led to granulomatous ileitis in Xiap −/− mice but not WT littermates. Conclusions: Our results demonstrate that XIAP deficiency is associated with susceptibility to microbiota-induced intestinal inflammation. These findings reinforce the notion of a critical role of PC defects and altered host–microbial interactions in the pathogenesis of CD, provide a mechanistic explanation to incomplete penetrance of CD in patients with XIAP mutations, and highlight the microbiota as a potential therapeutic target in patients with XIAP mutations and CD.